Responses of firms and households to government expenditure in Malaysia: evidence for the fuel subsidy withdrawal - Loo, Sze Ying; Mukaramah Harun (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper estimated the reactions of firms and households to the change of government expenditure from fuel subsidies to two alternative fiscal regimes, including the expansion of government expenditure on agricultural investment and direct cash transfers. Outcomes brought by the government expenditure changes to outputs of production for firms, together with the household consumption expenditure, were taken into account. This study was carried out by using a Löfgren-based computable general equilibrium (CGE) model. The findings showed that complete fuel withdrawal was found to have adverse impacts on firms and households. The withdrawal of subsidy brought a lackluster performance in domestic production. Firms that needed large amounts of fuel products to produce outputs were greatly affected. Besides, households of all segments faced large consumption loss. Nevertheless, the resulting adverse impacts on firms and households could be minimized with the implementation of mitigation measures along with the subsidy reform. The additional fund transfer to the agricultural sector had the merits of improving domestic production and minimizing the consumption loss of the population. In contrast, the direct cash transfer benefited the target population -- the medium- and low-income segments in the urban and rural areas.